Preparation of Ag-containing ACF and its Application for Dye Removal. Issue 3 (September 2017) - Yao, Lirong; Li, Xiaojuan; Zhang, Guangyu; Xu, Shanqing; Cheng, Dehong; Lu, Yanhua
Silver containing activated carbon fiber (Ag/ACF) has excellent adsorption properties for removing dyes. Silver particles are loaded onto ACF after carbonization and activation at present, and the fibers have low washing resistance and impurities are introduced onto ACF. In this research, pre-treatment techniques were used. Nano-silver solution with a particle size about 10 nm was prepared by using β-cyclodextrin as a stabilizer and reducer, and then the nano-silver solution was used as pretreatment liquid for modifying viscose fiber. Nano-silver particles with functional groups have high activity and can be readily adsorbed on the surface of viscose fibers. Ag/ACF was successfully prepared by carbonizing and activating the Ag-containing viscose fiber. The number and content of nano-silver particles on the surface of ACF was controlled by changing the concentration of nano-silver solution. The results show that the Ag/ACF have a high washing resistance and more efficiently remove methyl orange (MO) and methylene blue (MB) than ACF.